Uterine Cervix Cancer. Different Progress among Prevention, Early Diagnosis and Treatment - Víctor Manuel Medina Pérez; Rodolfo Arián Morales Yera; Liudmila Sierra Pérez (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
Cervix cancer constitutes one of the first causes of death for cancer in women in most poor and developing countries. It is, however, a preventable, treatable and potentially curable by organizational measures and early diagnosis. This disease has been associate to multiple risk factors, but with the improvement in the papilloma virus detection it was demonstrated that 98 % of the cases detected is due to this virus. New therapeutic strategies focus on molecular targets, inmunotherapy and the combination of these and old treatments as chemio-radio-therapy. Once again the issue of economy in cancer treatment is present, new therapies are highly expensive. Some countries, even when they allocate important budgets to their sanitary systems, do not have access to them.